International Consensus Recommendations on Microtia, Aural Atresia and Functional Ear Reconstruction - Zhang, Tian-yu (J Int Adv Otol, 2019)
The aim of this report is to provide international recommendations for functional ear reconstruction in patients with microtia and aural atresia. All patients with microtia and external auditory atresia should be seen in the setting of a multidisciplinary team and agreed treatment outcomes should be measured, so that techniques, approaches, and results can be compared. The methods are expert opinion from the members of the International Microtia and Atresia Workgroup (IMAW). The consensus recommendations reported herein take into account the variability in practice patterns present among experts in the field; the degree of consensus was quantified by presenting the percentage of above authors who agree or partially agree with each statement. Recommendations include the definition and classification of microtia/atresia, treatment of microtia, treatment of congenital aural atresia, flowchart of functional ear reconstruction, and future research directions. Patients with microtia and aural atresia can be guided by the consensus recommendations provided herein.